Godong Village Government's Leadership in Reducing Villager Mortality in the Covid-19 Pandemic - Maria Margareta Wardani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The paradigm of the spread of Covid-19 in Indonesia has made the central government act quickly to issue a Circular Letter of the Minister of Villages number 8 of 2020 concerning Covid-19 Response Villages and Affirmation of Village Cash Labor Intensive. The Governor of Central Java as the Chairperson of the Task Force for the Acceleration of Covid-19 Handling issued instruction Number 1 of 2020 concerning Community Empowerment in the Acceleration of Covid-19 Handling at the Citizens Association (RW) Level through the Establishment of the